Effect of Lycium Barbarum Polysaccharides (LBP) on the cognitive function of rats with type 2 diabetic encephalopathy - ZHAO,Liang (2022)
Abstract This study aims to explore the molecular mechanism of neuronal axonal lesions caused by high glucose, and to investigate the protective effect of Lycium barbarum polysaccharide (LBP) on neuronal axon damage with in vitro models. A rat model of type II diabetic encephalopathy was established, and the rats were treated with LBP for 10 weeks. Morris water maze experiment was used to detect spatial learning and memory ability. Neuronal axon lesions were measured by in vivo neuron tracing experiment. Immunohistochemistry and Western-blot technology were employed to detect protein localization and expression. Combined with in vitro primary neuron culture, total internal reflection fluorescence microscopy was used to detect the effects of high glucose and LBP on neuronal axon transport. PI3K inhibitors LY294002 and an activator of insulin signaling pathway were used to investigate the possible molecular mechanism. In vivo and in vitro experiments showed that in the hippocampus tissue of STZ-induced type II diabetic encephalopathy model rats, neuronal axons were damaged, accompanied by hyperphosphorylation of Tau protein, which subsequently resulted in axonal transport damage and cognition dysfunction. LBP significantly reduced peripheral blood glucose and serum insulin levels in type II diabetic encephalopathy model rats, thereby alleviating peripheral insulin resistance. At the same time, LBP can significantly improve the learning and memory impairment and brain neuron axon pathology in model rats. LY294002 treatment can effectively block the PI3K/Akt signaling pathway. The phosphorylation level of Tau protein in the LY294002+ LBP treatment group is higher than that of the LBP intervention group, while the insulin treatment can effectively reverse the blocking effect of LY294002 on LBPs. LBP can reduce the phosphorylation level of Tau protein by up-regulating the PI3K/Akt/GSK3β signaling pathway, with a protective effect on neuronal axon damage, thereby improving the cognitive function performance of type II diabetic encephalopathy model rats.